Analysis of the therapeutic efficacy of arthroscopic repair of the subscapularis tendon combined with coracoplasty - Hanlin Zheng; Yulong Liu; Bizhi Tu; Guang Chen; Rende Ning (Scientific Reports)
Abstract The aim of this study was to analyze the outcomes of arthroscopic subscapularis tendon repair combined with coracoplasty in the treatment. The study involved 80 patients (46 males, 34 females; aged 33 to 73 years), who underwent arthroscopic repair for subscapularis tears (type I, II, and III) presenting symptoms of anterior shoulder pain and tenderness. Subcoracoid impingement was defined as a coracohumeral distance of less than 6 mm on preoperative magnetic resonance imaging, with a follow-up of was at least two years. The patients were divided into two groups: Group A underwent coracoplasty, while Group B did not. The postoperative functional outcomes of the two groups were compared and analyzed using an independent sample t-test. The patients’ prognosis was assessed pre- and postoperatively using the University of California Los Angeles (UCLA) shoulder score, American Shoulder and Elbow Surgeons (ASES) shoulder score, and Visual Analog Scale (VAS)pain score. Postoperatively, primary wound healing was successful in all patients, with no systemic or localized shoulder joint infections or brachial plexus nerve injuries. Both groups showed improvements in overall functional outcomes after surgical intervention. At the 24-month follow-up, all evaluated parameters in both groups demonstrated improvements compared to preoperative values (P < 0.05). The functional scores significantly increased in both groups post-surgery compared to preoperative values (p < 0.01). When comparing the two groups using an independent sample t-test, the p-values for all indicators, except forward flexion range of motion, were below 0.01. The statistical analysis indicated that patients in Group A had better recovery outcomes than those in Group B, except for forward flexion. The results suggested that subcoracoid impingement syndrome could potentially be a significant precursor to subscapularis tendon injuries. It is noteworthy noting that the combined approach of subscapularis tendon repair and coracoplasty showed superior therapeutic efficacy compared to isolated subscapularis tendon repair when subscapularis tendon injuries were associated with subcoracoid impingement.